Electrospun Nanofiber-Based Ceramic Aerogels: Synergistic Strategies for Design and Functionalization - Panpan Li; Xuan Zhang; Ying Li; Cunyi Zhao; Jianyong Yu; Yang Si (Nano-Micro Letters)
Highlights This review provides comprehensive fabrication methods for the manufacturing of electrospun ceramic nanofibrous aerogels and offers professional guidance for materials development in this field. The optimization strategies for electrospun ceramic nanofibrous aerogels (ECNFAs)’ mechanical properties have been provided, highlighting multi-scale design from nano-building blocks to nanofiber aggregate structure design. This review systematically introduces the diverse roles of ECNFAs in specific application scenarios and application-specific mechanisms and provides transformative solutions for advanced engineering applications.